2021
DOI: 10.3947/ic.2021.0028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interferon Beta in COVID-19 adult patients: Systematic Review

Abstract: Background The high rate of transmission and infection of coronavirus disease 2019 (COVID-19) is a public health emergency of major epidemiological concern. No definitive treatments have been established, and vaccinations have only recently begun. We aim to review the efficacy and safety of Interferon Beta (IFN-β) in patients who have a confirmed COVID-19 diagnosis. Materials and Methods A search from PubMed, Science Direct, Cochrane, and Clinicaltrials.gov databases we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
(59 reference statements)
3
16
0
Order By: Relevance
“…calcineurin inhibitors) [ 1 ]. In contrast, SARS-CoV-2-infected children with genetic defects in innate immune responses, including type I IFN, may benefit from treatment with recombinant interferon [ 57 ] to help control viral replication in advance of a potential CSS. Genetics may thus tailor therapy for children with COVID-19 and MIS-C, but patient selection and timing of treatment will be critical.…”
Section: Cytokine Storm Syndrome Genes In Covid-19 and Multisystem Inflammatory Syndrome In Childrenmentioning
confidence: 99%
“…calcineurin inhibitors) [ 1 ]. In contrast, SARS-CoV-2-infected children with genetic defects in innate immune responses, including type I IFN, may benefit from treatment with recombinant interferon [ 57 ] to help control viral replication in advance of a potential CSS. Genetics may thus tailor therapy for children with COVID-19 and MIS-C, but patient selection and timing of treatment will be critical.…”
Section: Cytokine Storm Syndrome Genes In Covid-19 and Multisystem Inflammatory Syndrome In Childrenmentioning
confidence: 99%
“…Nakhlband et al [ 25 ] analysed the effect of IFN-β on LOHS in their meta-analysis, which included three studies, and found a significant reduction in the LOHS by IFN-β in comparison to control. Another systematic review by Sosa et al [ 26 ] also shows a decrease in overall hospital stay following addition of IFN-β to the current standard of care. However, WHO Solidarity trial found no significant difference in LOHS between groups of COVID-19 patients treated with IFN-β compared to standard of care [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the previously shown favorable effects of IL-6 blockade [53] and administration of IFNβ in hospitalized patients with COVID-19 [54] , together with the ying-yang observed between type I IFNs and IL-6 across sex and age groups, it would be tempting to hypothesize that concomitant administration of these agents could maximize therapeutic efficacy among high risk populations. However, such data are currently lacking.…”
Section: Discussionmentioning
confidence: 99%